The Biology and Ecology of Lygus Spp. On Cotton and Associated Crops - Butler, G. D. Jr. (College of Agriculture, University of Arizona (Tucson, AZ), 1970)
This item was digitized as part of the Million Books Project led by Carnegie Mellon University and supported by grants from the National Science Foundation (NSF). Cornell University coordinated the participation of land-grant and agricultural libraries in providing historical agricultural information for the digitization project; the University of Arizona Libraries, the College of Agriculture and Life Sciences, and the Office of Arid Lands Studies collaborated in the selection and provision of material for the digitization project.